An archaic Mexican shellmound and its entombed floors - Voorhies, Barbara (Monograph (Cotsen Institute of Archaeology at UCLA), 2015)
"Tlacuachero is the site of an Archaic-period shellmound located in the wetlands of the outer coast of southwest Mexico. This book presents investigations of several constructed floors, built during the 600-800 years of site formation in the Archaic period (ca. 8000-2000 BCE), the crucial timespan in Mesoamerican prehistory when people were transitioning from full blown dependency on wild resources to the use of domesticated crops. The constructed floors at the site are among the region's earliest permanent architecture, and are now deeply buried in a limited area within the shellmound. The authors explore what activities were carried out on their surfaces, discussing the floors' patterns of cultural features, sediment color, density and types of embedded microrefuse and phytoliths, as well as chemical signatures of organic remains. The studies conducted at Tlacuachero are especially significant in light of the fact that data-rich lowland sites from the Archaic period are extraordinarily rare; the wealth of information gleaned from the floors of the Tlacuachero shellmound can now be widely appreciated."--